2019
DOI: 10.1002/smtd.201800550
|View full text |Cite
|
Sign up to set email alerts
|

Boosting ORR/OER Activity of Graphdiyne by Simple Heteroatom Doping

Abstract: Nitrogen‐doped graphdiynes recently emerged as promising metal‐free oxygen reduction reaction (ORR) electrocatalysts. However, which type of N‐dopants contributing to the enhanced catalytic performance and the catalytic performances of other heteroatom‐doped graphdiynes has not been explored systematically. Herein, ORR and oxygen evolution reaction (OER) catalytic performances of X‐doped graphdiynes are examined by means of DFT computations (X = B, N, P, and S). It is revealed that the graphitic S‐doped graphd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(87 citation statements)
references
References 80 publications
3
80
0
Order By: Relevance
“…6a). According to the adjusted R square (R 2 ) of the fitted equations, the linear relationship between DG(OOH*) and DG (OH*) is better than that between DG(O*) and DG(OH*) [70,71]. Based on the scaling relations between DG(OOH*), DG(O*) and DG (OH*) fitted in Fig.…”
Section: O 2 Association Mechanismmentioning
confidence: 99%
“…6a). According to the adjusted R square (R 2 ) of the fitted equations, the linear relationship between DG(OOH*) and DG (OH*) is better than that between DG(O*) and DG(OH*) [70,71]. Based on the scaling relations between DG(OOH*), DG(O*) and DG (OH*) fitted in Fig.…”
Section: O 2 Association Mechanismmentioning
confidence: 99%
“…[191] The introduction of oxygen vacancies increases the charge density of ZnO resulting in the enhanced CO generation with j and maximum FE of −16.1 mA cm −2 and 83%, respectively at −1.1 V. Recently, oxygen vacancies on Cu-based catalysts can be tuned toward electrocatalytic CO 2 reduction to generate ethylene and ethanol. [192,193] Gu et al reported that partially reduced Cu oxide nanodendrites with surface-rich oxygen vacancies serving as excellent Lewis base sites for enhanced adsorption of *CO 2 and the release of *CH 2 which were further hydrogenated to form ethylene. [192] The maximum FE C2H4 and its corresponding partial j are 63% and −18.5 mA cm −2 , respectively at operating potential of −1.4 V. Similarly, we also proposed a strategy to produce a unique Adv.…”
Section: •−mentioning
confidence: 99%
“…[192,193] Gu et al reported that partially reduced Cu oxide nanodendrites with surface-rich oxygen vacancies serving as excellent Lewis base sites for enhanced adsorption of *CO 2 and the release of *CH 2 which were further hydrogenated to form ethylene. [192] The maximum FE C2H4 and its corresponding partial j are 63% and −18.5 mA cm −2 , respectively at operating potential of −1.4 V. Similarly, we also proposed a strategy to produce a unique Adv. Energy Mater.…”
Section: •−mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, N-doped graphite carbon material including activated carbon, carbon nanotubes and graphene [72,[101][102][103] have demonstrated to be the effective ORR catalysts. In this respect, the ORR process of N-atom-doped GDY on the cathode of a fuel cell was also discussed in many studies [104][105][106][107][108][109][110][111]. The ORR mechanism of N-doped GDY was investigated by using the first principles calculations.…”
Section: Nonmetallic-atom-doped Gdy Electrocatalystsmentioning
confidence: 99%